Phân tích thành nhân tử a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2)-2abc-a^3-b^3-c^3
phân tích thành nhân tử a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2)-2abc-a^3-b^3-c^3
Phân tích thành nhân tử
a, a(a+b)-bc(b+c)+ca(c+a)+abc
b, a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2)+2abc
c, a^3(b-c)+b^3(c-a)+c^3(a-b)
Phân tích thành nhân tử
a, a(a+b)-bc(b+c)+ca(c+a)+abc
b, a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2)+2abc
c, a^3(b-c)+b^3(c-a)+c^3(a-b)
Phân tích đa thức thành nhân tử:
\(a\left(b^2+c^2\right)+b\left(c^2+b^2\right)+c\left(a^2+b^2\right)-2abc-a^3-b^3-c^3\)
Phân tích đa thức thành nhân tử
\(a\left(b^2+c^2\right)+b\left(c^2+a^2\right)+c\left(a^2+b^2\right)-2abc-a^3-b^3-c^3\)
Phân tích thành nhân tử :
a(b2 + c2) + b(c2 + a2) + c(a2 + b2) - 2abc - a3 - b3 - c3
Phân tích thành nhân tử :
a, \(a\left(b^2+c^2\right)+b\left(a^2+c^2\right)+c\left(a^2+b^2\right)+2abc\)
b, \(a^3-b^3-c^3-3abc\)
a)a(b2+c2)+b(a2+c2)+c(a2+b2)+2abc
=ab2+ac2+ba2+bc2+ca2+cb2+2abc
=(ab2+ba2)+(ac2+bc2)+(ca2+abc)+(cb2+abc)
=ab(a+b)+c2(a+b)+ca(a+b)+cb(a+b)
=(a+b)(ab+c2+ca+cb)
=(a+b)(a+c)(b+c)
b)a3-b3-c3-3abc
=(a-b)3-c3+3ab(a-b)-3abc
=(a-b-c)[(a-b)2+(a-b)c+c2]+3ab(a-b-c)
=(a-b-c)(a2-2ab+b2+ac-bc+c2+3ab)
=(a-b-c)(a2+b2+c2+ab-bc+ca)
phân tích thành nhân tử
a2b+a2c+b2a+b2c+c2a+c2b - 2abc -a3-b3-c3
Phân tích thành nhân tử :
c, a^2 b^2(a-b) +b^2 c^2(b-c) +c^2 a^2(c-a)
d, a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2) -2abc-a^3-b^3-c^3
e, a^4(b-c)+b^4(c-a)+c^4(a-b)
c) \(a^2b^2\left(a-b\right)+b^2c^2\left(b-c\right)+c^2a^2\left(c-a\right)\)
\(=a^2b^2\left(a-b\right)+b^2c^2\left(b-c\right)-c^2a^2\left[\left(a-b\right)+\left(b-c\right)\right]\)
\(=a^2b^2\left(a-b\right)+b^2c^2\left(b-c\right)-c^2a^2\left(a-b\right)-c^2a^2\left(b-c\right)\)
\(=\left(a-b\right)\left(a^2b^2-c^2a^2\right)+\left(b-c\right)\left(b^2c^2-c^2a^2\right)\)
\(=a^2\left(a-b\right)\left(b-c\right)\left(b+c\right)+c^2\left(b-c\right)\left(b-a\right)\left(a+b\right)\)
\(=\left(a-b\right)\left(b-c\right)\left[a^2\left(b+c\right)-c^2\left(a+b\right)\right]\)
\(=\left(a-b\right)\left(b-c\right)\left(a-c\right)\left(ab+bc+ca\right)\)